"Ever Vigilant" in "Ethically Impossible". (6th May 2013) - Galarneau, Charlene
Abstract The report from the Presidential Commission for the Study of Bioethical Issues is clear that the public health services research conducted in Guatemala mid‐century was wrong, but its focus on individual responsibilities is inadequate for the structural and institutional factors at the root of that research. Ethically Impossible": STD Research in Guatemala from 1946 to 1948, released in September 2011 by the Presidential Commission for the Study of Bioethical Issues, 1 responds to President Obama's request for a "thorough fact‐finding investigation" into research carried out by the U.S. Public Health Service in Guatemala from 1946 to 1948. "Ethically Impossible" offers a detailed narrative of what happened in Guatemala and a self‐described "unvarnished ethical analysis." I argue, however, that being "ever vigilant" to prevent exploitation, as well as learning as a society from this past and honoring the memory of Guatemalan victims, requires a more complex ethical analysis than the commission offers in this report. Specifically, we need to identify the structural injustices that innervated the social relations and the institutions fundamental to the moral landscape of this 1940s research, and we need to expand our understandings of moral responsibility accordingly. The report posits three "longstanding and widely accepted moral principles" as the framework for evaluating this research: (1) to treat persons fairly and with respect, (2) not to harm (or risk harming) persons unless the risk is reasonable and the benefit proportional, and (3) not to treat persons as means to others' ends. As critically important as the three principles are to research ethics writ large, they alone are unfitting tools for addressing the kind of structural and institutional moral factors that are so important in these PHS studies.